Pemberdayaan Budidaya Madu Trigona Untuk Kesejahteraan Ekonomi dan Upaya Menopang Keberadaan Taman Wisata Trigona Di Desa Batulayar - Mashur, Mashur; Riswandi, Dedi; Haryadi, Herjan; Febriani, Suryati; Nada, Husna (Jurnal Gema Ngabdi, 2024)
Honey cultivation can be used for economic value and of course makes a real contribution to the economic community. For people who have a strong determination to develop Trigona honey cultivation, it is useful as an additional business. Honey cultivation activities can also be designed in the form of a honey cultivation business group. This fact shows that in these conditions it is necessary to make efforts to carry out empowerment activities, namely to encourage people to have knowledge and skills so that interest and motivation in Trigona honey cultivation activities grows. Also to encourage people to earn additional income. Through this PKM-PMP, in collaboration with the Batulayar village government, the aim is to provide empowerment activities for Trigona honey cultivation. Empowerment activities are carried out through the socialization stages of empowering honey cultivation and training activities through collaboration and digital literacy for the economic welfare of the community. The activity showed good results, based on the results of the pretest and posttest with a good category of an average of 56.4%-92.7%.